Development and Validation of a Video-Based Passing Decision-Making Test for Soccer and Futsal (Baltic Journal of Sport and Health Sciences, 2024)
Background: Success in team sports such as soccer and indoor soccer depends heavily on the ability to make accurate and quick decisions due to the dynamic and unpredictable nature of game conditions. This study aimed to create and verify a video-based test that evaluates decision making abilities in players participating in soccer and futsal (VPD SocFut).Methods: The test was carefully designed using real-world video clips and underwent rigorous validation procedures that included content validity checks as well as assessments, for test retest reliability, construct and face validity.Results: Content validity was ensured through two phases of expert evaluation of video clips, resulting in the selection of soccer and futsal clips that demonstrated 70% to 100% agreement in decision appropriateness and difficulty. Reliability was confirmed via test-retest measures, with Cohen’s Kappa values ranging from 0.402 to 1.000. Construct validity was supported by significant differences in passing decision-making performance between subelite and recreational adult and U18 soccer and futsal players (p < .001). Participants consistently rated the test as realistic and enjoyable, which confirmed its face validity.Conclusion: Therefore, the VPD-SocFut suggests a reliable and valid tool for objectively evaluating passing decision-making performance in soccer and futsal.Keywords: soccer, performance, decision-making, testing.